DESAIN UNTUK HOT PLATE MAGNETIK STIRRER DENGAN MOTOR RPM TINGGI - Muhammad Ulin Nuha ABA; Abdul Haris Kuspranoto; Muslihun; Riza Saktira P.S; Imam Tri Harsoyo (MEDIKA TRADA, 2024)
Hotplate magnetic stirrer is laboratory equipment used to mix solutions to make them more homogeneous by utilizing a heater and magnetic rod controlled by a high RPM motor, as well as several other supporting components. All these components are assembled into one good tool. In order to produce a good magnetic stirrer hotplate tool, it is necessary to make a planning design to produce a magnetic stirrer hotplate tool that is ergonomic and functional. In designing this tool, several stages of literature study are carried out, designing the tool (to find out the various components needed), designing the tool using a computer, printing the tool, installing components and testing the electrical power of the tool. Based on these steps, the casing design for the Hotplate Magnetic Stirrer tool was successfully created with a length = 230 mm, width = 220 mm, and height = 156 mm. This casing design is able to accommodate all electronic and non-electronic components used, especially high RPM DC motors. It is proven that through this casing design, the high RPM DC motor and other components are installed (attached) well. It has also been confirmed that all installed electronic components have voltage according to their specifications. Keywords: Magnetic Stirrer Hotplate, Design, Motor, RPM, Components.